Assessment of earthquake-induced liquefaction hazard in urban areas of Hanoi city using LPI-based method - Nhung, Bui Thi; Phuong, Nguyen Hong; Truyen, Pham The; Nam, Nguyen Ta (Vietnam Journal of Earth Sciences, 2018)
Liquefaction Potential Index (LPI) is used as an assessing tool of liquefaction potential. In this study, the LPI-based method was applied to evaluate the earthquake-induced liquefaction potential for the urban area of Hanoi city. The data used includes 120 boreholes logs, containing necessary geomechanical information such as fine contents, specific gravity, dry density, porosity, N (SPT) values and the groundwater depth Z(w) of subsoil layers in every borehole. The “simplified procedure” proposed by Seed and Idriss was applied to evaluate the liquefaction of all subsoil layers in each borehole point. Then, the Liquefaction Potential Index was calculated for the whole soil column at al boreholes points using the method proposed by Iwasaki. Finally, the obtained LPI values were used to assess the liquefaction probability for an urban area of Hanoi city, using the empirical formula proposed by Papathanassiou and two earthquake scenarios originated on the Chay river fault with magnitudes of 5.3 and 6.5, respectively.For entire study area, the first scenario earthquake (Mw=5.3) is not capable of causing liquefaction (PG<0.1). This means that the downtown area of Hanoi city is non-liquefiable to the medium magnitude events. Results of the second scenario (Mw=6.5) show in worst cases, an earthquake with magnitude, maximum expected for Hanoi region can produce liquefaction throughout the downtown area of Hanoi city. The highest liquefaction probability of 0.7<PG≤0.9 is distributed in two large areas, where the first one is observed in Thanh Tri district, eastern part of Ha Dong, a smaller areas of the Thanh Xuan, Tu Liem and Cau Giay districts, while the second area covers Hoan Kiem district, a northern part of Hai Ba Trung district and northwestern part of Long Bien district.This is the first time the LPI based method was applied for evaluation of earthquake-induced liquefaction for Hanoi city. The most advantage of the method is that it can be easy to use, although the reliability of the results depends very much on number and distribution of the borehole data. Nevertheless, the combination of this method with other available methods can help effectively solving the problem of urban seismic risk assessment for the mega-cities in Vietnam.References Bui Cong Que, 1983. The new results in study of the crustal Structure for the territory of Vietnam. J. Sci. of the Earth, 5(1), 17-24 (in Vietnamese).Bui Van Duan, Nguyen Cong Thang, Nguyen Van Vuong, Phạm Dinh Nguyen, 2013. The magnitude of the largest possible earthquake in the Muong La- Bac Yen fault zone. J. Sci. of the Earth, 35, 49-53 (in Vietnamese).Day R.W., 2002. Geotechnical Earthquake engineering Handbook. McGRaw-Hill New York Chicago San Francisco Lisbon London Madrid Mexico City Milan New Delhi San Juan Seoul Singapore Sydney Toronro. Printed and bound by R.R. Donnelley & Sons Company.Dixit J., Dewaikar D.M.and Jangid R.S., 2012. Assesment of liquefaction potential index for Mumbai city. Nat. Hazards Earth Syst. Sci., 12, 2759-2768.Federal Emergency Management Agency, 1999. NEHRP recommended Provisions for Seismic Regulations for New Buildings, Washington, D. C., Developed by the Building Seismic Safety Council (BSSC) for the Federal Emergency Management Agency (FEMA).Gillins D.T., 2016. Probabilistic Liquefaction Potential and Lateral Spread Hazard Maps for Utah County, Utah: Collaborative Research with Brigham Young University and Oregon State University. USGS Award Numbers: G14AP00118 & G14AP00119.Term of Award: 08/01/2014 - 01/31/2016.Tran Dinh Hoa and Bui Manh Duy, 2013. Earthquake-induced liquefaction foudation and the methods of assessment for liquefaction foundation for Kinh Lo barrier Ho Chi Minh City. Journal of Water Resources Science and Technology, 15(4), 21-29.Ishihara K., 1985. Stability of natural deposits during earthquakes. Proceedings of the 11th International Conference on Soil Mechanics and Foundation Engineering, 1. A.A. Balkema, Rotterdam, The Nertherlands, 321-376.Iwasaki T., Tatsuoka F., Tokida K. and Yasuda S., 1978. A practicalmethod for assessing soil liquefaction potential based oncase studies at various sites in Japan, In Proceedings of the 2nd International Conference on Microzonation for Safer Construction-Research and Application, San Francisco, Calif., 26 November-1 December. American Society of Civil Engineers, New York, 2, 885-896.Iwasaki T., Arakawa T. and Tokida K., 1982. Simplified proceduresfor assessing soil liquefaction during earthquakes. InProceedingsof the Conference on Soil Dynamics and EarthquakeEngineering, Southampton, UK, 13-15 July 1982. Balkema,Rotterdam, the Netherlands, 925-939.Kircher C.A., Whitman R.V., Holmes W.T., 2006. HAZUS earthquake loss estimation methods. Nat Hazards Rev, 7(2), 45-59.Kongar I., Rossetto T., Giovinazzi S., 2016. Evaluating Simplified Methods for Liquefaction Assessment for Loss Estimation. Nat. Hazards Earth Syst. Sci. Discuss. Doi:10.5194/nhess-2016-281.Li D.K., Juang C.H. and Andrus R.D., 2006. Liquefaction potentialindex: a critical assessment, Journal of GeoEngineering,Taiwan Geotechnical Society, 1(1), 11-24.Liu F., Li Z., Jiang M., Frattini P. and Crosta G., 2016. Quantitative - induced lateral spead hazard mapping. Engineering Geology, 207, 36-47. Doi: 10.1016/j.enggeo.2016.04.001.Mustafa Erdik, K. S˘es˘etyan, M.B. Demirciog˘lu, C. Zu¨lfikar, U. Hancılar, C. Tu¨zu¨n, and E. Harmandar., 2014. Rapid Earthquake Loss Assessment After Damaging Earthquakes. Perspectives on European Earthquake Engineering and Seismology, 1, 53-95.Nguyen Hong Phuong, 2000. An algorithm for seismic risk assessment in Vietnam using a GIS. J. Sci. of the Earth, 22(3), 210-222 (in Vietnamese).Nguyen Hong Phuong (Project Manager), 2002. Study of seismic risk of Hanoi city. Project code 01C-04/09-2001-2. Institute for Marine Geology and Geophysics, VAST.Nguyen Hong Phuong, 2003. Development of a DSS for seismic risk assessment and Loss reduction using GIS technology. Contributions of the Marine Geophysics and Geology, VII, 62-78 (in Vietnamese).Nguyen Hong Phuong (Project Manager), 2003. Study of seismic risk of Hanoi city. Final report of the National scientific research Project 01C-04/09-2001-2, Hanoi (in Vietnamese).Nguyen Hong Phuong (Project Manager), 2007.  Application of GIS technology to Development of a model for seismic risk analysis for Hanoi city. Final Report of Research Project, Institute for Marine Geology and Geophysics, VAST.Nguyen Hong Phuong, 2008. Assessment of earthquake risk for Ho Chi Minh city using GIS and mathematical models. Final Report of Research Project, Institute of Geophysics, VAST (in Vietnamese).Nguyen Hong Phuong, 2009. Integrated Spatial decision support Systems for Urban Emergencies (ISSUE), Final Report of Vietnam-French Research Project, Hanoi.Nguyen Huy Phuong (Project Manager), 2010.  Study on the phenomenon of coherent action and changes reliability of   Hanoi bottom land under the impact of dynamic load in order to improve the geotechnical information system for sustainable development and disaster prevention. Hanoi University of Mining and Geology.Nguyen Hong Phuong (Project Manager), 2014.  Estimation of Site Effects and Assessment of Urban Seismic Risk for Hanoi city. National Scientific Research Project Final report. Institute of Geophysics, VAST.Papathanassiou G., 2008. LPI-based approach for calibrating theseverity of liquefaction-induced failures and for assessing theprobability of liquefaction surface evidence. Engineering Geology, 96(1-2), 94-104. Doi:10.1016/j.enggeo.2007.10.005.Phan Trong Trinh, Hoang Quang Vinh, Leloup Philippe Hervé, Giuliani G., Vincent Garnier., Tapponnier P., 2004. Cenozoic deformation, thermodynamic evolution, slip mechanism of Red River shear zone and ruby formation. Science and Technics Publishing House, Hanoi, 5-72 (In Vietnamese with English abstract).Phan Trong Trinh, Ngo Van Liem, Nguyen Van Huong, Hoang Quang Vinh, Bui Van Thom, Bui Thi Thao, Mai Thanh Tan, Nguyen Hoang, 2012. Late Quaternary tectonics and seismotectonics along the Red River fault zone, North Vietnam. Earth-Science Reviews, 114, 224-235.Phan Trong Trinh, Hoang Quang Vinh, Nguyen Van Huong, Ngo Van Liem, 2013. Active fault segmentation and seismic hazard in Hoa Binh reservoir, Vietnam. Cent. Eur. J. Geosci., 5(2), 223-235.Jaimes M.A, Niño M., Reinoso E., 2015. Regional map of earthquake-induced liquefaction hazard using the lateral spreading displacement index DLL, 77, 1595-1618.Juang C.H., et al., 2002. Assessing Probability-based Methodsfor Liquefaction Potential Evaluation. Journal of geotechnical and Geoenvironmental Engineering, 128(7), 580-589.Juang C.H., Yang S.H., Yuan H., Fang S.Y., 2005. Liquefaction inthe Chi-Chi earthquake: effect of fines and capping non-liquefiablelayers. Soils and Foundations, 45(6), 89-101.Juang C.H., Li D.K., 2007. Assessment of liquefaction hazards in Charleston quadrangle South Carolina. Engineering Geology, 92, 59-72. Doi:10.1016/j.enggeo.2007.03.003.Juang C.H., Chang Y.O., Lu C.C., Luo Z., 2010. Probabilistic framework for assessing liquefactionhazard at a given site in a specified exposure timeusing standard penetration testing. Canadian Geotechnical Journal, 47(6), 674-687. https://doi.org/10.1139/T09-127.Seed H.B., and  Idriss I.M., 1971. Simplified procedure for evaluatingsoil liquefaction potential. Journal of the Soil Mechanics andFoundations Division, ASCE, 97(9), 1249-1273.Vu Thanh Tam (Project Manager), 2014. Study and propose a reasonable threshold for preventing the subsidence caused by ground water exploitation, pilot application for downtown area of the Hanoi city. Final report of the Scientific research and technology development Project, National Center for water resource planning and investigation. Ministry of Natural Resources and Environment.Nguyen Ngoc Thuy (Project manager), 2004. “Study, supplement and enhancement of the 1:25,000 scale seismic microzonning map of the expanded Hanoi city, development of the ground motion characteristics database in Hanoi in accordance with the map”. Final report of the scientific research project, The Hanoi Institute of Building Technology. Hanoi Construction Department.Whitman R.V., Anagnos T., Kircher C.A., Lagorio H.J., Lawson R.S., Schneider P., 1997. Development of a national earthquake loss estimation methodology. Earthquake Spectra, 13(4), 643-661.Nguyen Dinh Xuyen, 1987. Manifestation of strong earthquake activity in the territory of Vietnam, J. Sci. of the Earth, 9(2), 14-20 (in Vietnamese).Nguyen Dinh Xuyen, Nguyen Ngoc Thuy et al., 1996. Completion of the seismic microzoning map of 1:25 000 scale for Hanoi region. Final report of the City’s level project. Institute of Geophysics, Hanoi (in Vietnamese).Nguyen Dinh Xuyen (Project Manager) 2004. Final report of the National scientific research project on “Study of earthquake prediction and ground motion in Vietnam”, Institute of Geophysics, Hanoi (in Vietnamese).Youd T.L., Idriss I.M., Andrus R.D., Arango I., Castro G., Christian J.T., Dobry R., Finn W.D.L., Harder L.F., Hynes M.E., Ishihara K., Koester J.P., Liao S.S.C., Marcurson III W.F., Marti G.R.,Mitchell J.K., Moriwaki Y., Power M.S., Robertson P.K., Seed R.B., Stokoe II K.H., 2001. Liquefaction resistance of soils: summary report from the 1996 NCEER and 1998 NCEER/NSFworkshops on evaluation of liquefaction resistance of soils. Journalof Geotechnical and Geoenvironmental Engineering, ASCE, 127(10), 817-833.Yuan H., Yang S.H., Andrus R.D., Juang C.H., 2004. Liquefaction-inducedground failure: A study of the Chi-Chi earthquake cases. Engineering Geology, 71(1-2), 141-155.